Pre-Reading Activities For Muslim and Non-Muslim Students - Wijaya, M. Sayid (English Education: Jurnal Tadris Bahasa Inggris, 2016)
This article tries to propose some possible pre-reading activities in teaching reading comprehension for Muslim and non-Muslim students, especially for junior high school students. Since the teachers directly have their students read the text without noticing any appropriate pre-reading activities which can help them activate their prior knowledge makes them hard to make meaning of new information they are to obtain from the text. Therefore, designing pre-reading activities which is appropriate to the reading materials becomes a priority. Integrating pre-reading activities such as Think Sheet and Scanning greatly affects students’ ability in comprehending new information containing in the text.